Factors Influencing Consumptive Behavior of Students of UPT SMA Negeri 5 Parepare - Nurhamida Nurhamida; Syahriyah Semaun; Firman Firman; Suarning Suarning; Damirah Damirah (Jurnal Ilmu Manajemen Profitability, 2024)
A description of the consumer behavior of SMA Negeri 5 Parepare students is the aim of this research. Consumer behavior is the dependent variable, and financial literacy, hedonic lifestyle, and social environment are factors that influence it. Field research is a type of research whose research method uses quantitative descriptive research. The total population was 387 people, and 80 samples were taken. Questionnaires are used in research to obtain data. The research results show: Based on the results of the t test, it shows that there is an influence between Financial Literacy and Consumptive Behavior with a value of 0.000 0.05, so H1 is accepted. There is an influence of Lifestyle on Consumptive Behavior with a value of 0.001 0.05, so H2 is accepted. Furthermore, there is no influence between the Social Environment and Consumer Behavior with a value of 0.115 0.05, so H3 is rejected. Furthermore, the variable that most dominantly influences Consumptive Behavior is the Financial Literacy variable with a value of 0.868.